2016
DOI: 10.1093/restud/rdw042
|View full text |Cite
|
Sign up to set email alerts
|

Productivity and Quality in Health Care: Evidence from the Dialysis Industry

Abstract: We show that healthcare providers face a tradeoff between increasing the number of patients they treat and improving their quality of care, with those providers facing the strongest incentives to treat more patients delivering the lowest quality of care. To measure the magnitude of this quality-quantity tradeoff, we estimate a model of dialysis provision that explicitly incorporates a center's endogenous choice of treatment quality and allows for unobserved differences in productivity across centers. We find t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 33 publications
1
42
0
Order By: Relevance
“…Dialysis facilities with more capacity may have more time and resources available for facility staff to take necessary antiseptic precautions and address patients’ needs. An economic analysis of the trade‐off between quality and quantity in dialysis care found that, when facilities choose to dialyze more patients for a given amount of fixed inputs (including dialysis stations), patients are more likely to develop serious infections (Grieco and McDevitt ). An association between market competition, dialysis facility capacity, and infections is consistent with our finding that the probability of hospitalization for infection was slightly higher in less competitive markets.…”
Section: Discussionmentioning
confidence: 99%
“…Dialysis facilities with more capacity may have more time and resources available for facility staff to take necessary antiseptic precautions and address patients’ needs. An economic analysis of the trade‐off between quality and quantity in dialysis care found that, when facilities choose to dialyze more patients for a given amount of fixed inputs (including dialysis stations), patients are more likely to develop serious infections (Grieco and McDevitt ). An association between market competition, dialysis facility capacity, and infections is consistent with our finding that the probability of hospitalization for infection was slightly higher in less competitive markets.…”
Section: Discussionmentioning
confidence: 99%
“…The dialysis capacity in a given market (HSA), as measured by the number of dialysis stations operated, is practically a permanent decision for each dialysis provider; the data available typically report little subsequent adjustment in capacity by providers following initial entry into a market. Grieco and McDevitt (2014) find that dialysis capacity remained constant for over 90% of the dialysis facilities in the United States between 2004 and 2007.…”
Section: A Dialysis and Capacitymentioning
confidence: 94%
“…The empirical literature, however, has largely ignored the strategic incentives in the continuous choices of capacity. With little price and quality competition (as shown in Grieco &McDevitt, 2013, andCutler et al, 2012), these strategic incentives are important for dialysis providers. 3 In practice, a dialysis provider's margin decreases in the capacity of competitors.…”
Section: Introductionmentioning
confidence: 99%
“…TFP is exogenous to the hospitals' inputs composition, so that it explains output differences not attributable to labor, capital or material expenses. Instead, TFP incorporates unobservable aspects of hospitals' operations, such as managerial ability and inputs quality (Grieco and McDevitt, 2012). Solow (1957) presented the theoretical foundations of TFP, which he describes as a pure scale effect that is exogenous to the inputs' marginal rates of substitution that are incorporated in the production function.…”
Section: Hypotheses On Conflictmentioning
confidence: 99%
“…The empirical estimation of TFP is obtained through the so‐called Solow Residual. Grieco and McDevitt (2012) have been one of the latest to apply this concept in the study of the relationship between productivity and quality in healthcare. We estimate TFP as a fixed term, TFP i , for every hospital in the sample, which is obtained as the residual of a Cobb‐Douglas production function (3).…”
Section: Empirical Modelmentioning
confidence: 99%